Modeling the motion of a ship with suspended cargo - Solovyov A. A.; Shugay S. N. (Vestnik MGTU)
The stability of a vessel determines its ability to safely navigate in any sea state. In the process of studying the dynamics of a vessel in rough seas, the method of mathematical modeling based on the linear theory of waves and rolling has been used. The models allow obtaining calculation formulas and methods used to analyze the rolling of vessels with shifting cargo on board (liquid, bulk, suspended). The effect of suspended cargo on the seaworthiness of a vessel is currently considered only when solving problems of static stability. When solving problems of dynamics, mathematical models of the roll of a vessel with suspended cargo in calm water and regular waves have been proposed, and linear differential equations of the roll of a vessel with suspended cargo have been obtained. The presence of suspended cargo on a vessel significantly changes the parameters of the roll due to the occurrence of heeling and variable moments of inertia of the vessel. The proposed mathematical methods allow simulating the roll in any regular waves, taking into account arbitrary values of the transverse metacentric height, cargo weight and suspension length.